Silent Icelandicrete : Icelandic biomaterial research - Viltė Adomavičiūtė 1987- (2023)
This research explores the usage of Iceland’s local natural building materials for sustainable interior architecture and the development of new biomaterials using hemp shiv as the primary component. Since the majority of people spend a lot of their time indoors, ensuring safe and healthy living conditions are crucial. It took several decades for society to recognize the value of sustainability in construction and environment. In the quest for enhanced construction techniques, there arises a need to explore novel materials. A promising option, which boasts desirable technical attributes and relies on renewable resources, is hemp shiv concrete - also known as hempcrete. This construction material is composed of hemp shives, lime, and water. Limestone is a non-native resource in Iceland, so this research explores which local Icelandic materials could act as a binder in combination with hemp shives to create a sound-absorbing material. Historically, Icelanders built from turf and basalt, or other volcanic rock. Yet another underutilized/unused, interesting material that is abundant in Iceland is seaweed. This research shows the usability of seaweeds as binding agents and demonstrates that Laminaria Digitata seaweed is a viable option for use as a binder in hemp shiv-based biomaterial blends. The study highlights the potential of these blends for sound-absorbing design objects in contemporary interiors. By utilizing local, renewable resources, this study contributes to sustainable interior architecture practices while also showcasing the implementation of the innovative potential of natural building materials.